Impact of model free parameters and sea‐level rise uncertainties on 20‐years shoreline hindcast: the case of Truc Vert beach (SW France). Issue 8 (26th March 2020) - D'Anna, Maurizio; Idier, Déborah; Castelle, Bruno; Le Cozannet, Gonéri; Rohmer, Jeremy; Robinet, Arthur
Abstract: Shoreline change is driven by various complex processes interacting at a large range of temporal and spatial scales, making shoreline reconstructions and predictions challenging and uncertain. Despite recent progress in addressing uncertainties related to the physics of sea‐level rise, very little effort is made towards understanding and reducing the uncertainties related to wave‐driven shoreline response. To fill this gap, the uncertainties associated with the long‐term modelling of shoreline change are analysed at a high‐energy cross‐shore transport dominated site. Using the state‐of‐the‐art LX‐Shore shoreline change model, we produce a probabilistic shoreline reconstruction, based on 3000 simulations over the past 20 years at Truc Vert beach, southwest France, whereby sea‐level rise rate, depth of closure and three model free parameters are considered uncertain variables. We further address the relative impact of each source of uncertainty on the model results performing a Global Sensitivity Analysis. This analysis shows that the shoreline changes are mainly sensitive to the three parameters of the wave‐driven model, but also that the sensitivity to each of these parameters is strongly modulated seasonally and interannually, in relation with wave energy variability, and depends on the time scale of interest. These results have strong implications on the model skill sensitivity to the calibration period as well as for the predictive skill of the model in a context of future climate change affecting wave climate and extremes. © 2020 John Wiley & Sons, Ltd. Abstract : The effect of uncertainties in sea‐level rise (SLR) rate, depth of closure (DoC) and shoreline model free parameters on a 20‐year shoreline hindcast using a state‐of‐the‐art shoreline change model LX‐Shore is analysed performing a variance‐based Global Sensitivity Analysis. This approach is applied to the high‐energy, cross‐shore dominated sandy beach of Truc Vert, SW France.